ANALISIS KUALITAS PELAYANAN TERHADAP CAKUPAN ANTENATAL CARE (ANC) DI PUSKESMAS JATIJAJAR KOTA DEPOK TAHUN 2019 - Triana Indrayani; Ria Pusvita Sari (Universitas Nasional, 2020)
Background: WHO has set standards in conducting Antenatal Care, at least 4 times during pregnancy. To see the number of pregnant women who have already done Antenatal Care, which is the result of achieving the coverage indicators of K1 and K4 services. Based on data obtained from the Jatijajar Health Center data for the last two years, where MCH services from 2017 K1 visits were 60.9% and K4 coverage was 60.2%. In 2018 K1 visits were 82.93% and K4 coverage was 61 66%. Aim: to identify the quality of service on Antenatal coverage in the jatijajar Public Health Center Depok City 2019 Methodology: a cross sectional was used, the population were all of the pregnant women who lived in the Jatijajar Public Health Center Depok City 2019. An accidental sampling was used. There were 80 respondents. A questionnaire was used. Results: the results showed that there was a significant relationship between tangible service quality (Physical Evidence) and coverage of Antenatal care services obtained by statistical test results p value 0.01 <0.05, reliability showed p value 0.00 <0.05, responsiveness showed a p value of 0.01 <0.05, assurance showed a p value of 0.05 <0.05 and empathy indicated a p value of 0.00 <0.05. Conclusion and suggestion: service quality can affect the coverage of Antenatal Care so that health workers must improve the quality of services that have been applied in the coverage of Antenatal Care services and other services.